2017
DOI: 10.1002/iid3.151
|View full text |Cite
|
Sign up to set email alerts
|

In vivo targeting of protein antigens to dendritic cells using anti‐DEC‐205 single chain antibody improves HIV Gag specific CD4+ T cell responses protecting from airway challenge with recombinant vaccinia‐gag virus

Abstract: Thus targeting protein antigens to DCs using scDEC can be used either alone or in combination with other strategies for effective immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…These results are in agreement with those obtained by others showing that in combination with TLR stimulation, DEC205 targeting induced a robust CD4+ T cell immune response ( 47 49 ) and only low level of CD8+ T cell response ( 25 , 40 ). One exception is OVA protein for which both potent CD4+ and CD8+ responses were obtained ( 39 , 50 , 51 ). In fact, previous reports have more focused on mapping CD4+ T cell epitopes to SAG1t.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with those obtained by others showing that in combination with TLR stimulation, DEC205 targeting induced a robust CD4+ T cell immune response ( 47 49 ) and only low level of CD8+ T cell response ( 25 , 40 ). One exception is OVA protein for which both potent CD4+ and CD8+ responses were obtained ( 39 , 50 , 51 ). In fact, previous reports have more focused on mapping CD4+ T cell epitopes to SAG1t.…”
Section: Discussionmentioning
confidence: 99%
“…Human CD4 + and CD8 + T cell recognition of EBNA1 carrying or encoding vaccine formulations. It has been previously demonstrated that targeting antigens to the type I transmembrane multilectin receptor DEC205 that is preferentially expressed on conventional type 1 DCs (cDC1s) leads to prominent CD4 + T cell responses but has only a subtle effect on CD8 + T cell induction in vitro and in vivo (21)(22)(23)(24). To potentially identify a more suitable receptor for enhanced antigen delivery to both MHC class I and II pathways, we constructed fusion proteins of EBNA1 and Abs directed at 9 other receptors with different internalization kinetics and expressed by similar or different myeloid cell subsets (as indicated in parentheses): BDCA3 (cDC1s), CD206 (monocytes), CD207 (Langerhans cells and dermal cDC1s), CD209 (DCs), CD40 (all antigen-presenting cells), HLA-DR (all antigen-presenting cells), CD1c (cDC2s), and CD11c (in blood, primarily DCs).…”
Section: Resultsmentioning
confidence: 99%
“…Selective targeting of ovalbumin (Ova) antigen to DCs using recombinant scDEC-Ova also resulted in much higher antigen uptake and presentation to both CD8 + and CD4 + T cells compared to soluble Ova. The same group also found strong and long-lasting specific CD4 + T cells when they targeted DCs with scDEC-Gag protein plus poly ICLC vaccine [63]. In a recent study, targeting DEC205 with a DC specific adenoviral vector expressing human glioma specific antigen showed prolonged survival in a murine glioma tumor model [64].…”
Section: Targeting Different Dcs Receptors For Vaccine Developmentmentioning
confidence: 99%